Complexity of concussion management in youth ice hockey: Context matters - Black, A. M.; Omu, O.; Brussoni, M.; Emery, C. A. (Translational Sports Medicine, 2021)
The public's concussion awareness is increasing. However, youth may still participate in sport through concussion symptoms and parents may not take their child with a suspected concussion to a physician for assessment and clearance to return to sport. This study uses qualitative methodology to explore parent and coach experiences with concussion management in youth ice hockey. Potential barriers and facilitators to a coach removing a player from play following a suspected concussion and parents taking their child to see a physician are highlighted. We purposively selected twenty-four hockey parents and coaches in Calgary, Canada, and interviewed them to understand their experience managing youth following a suspected concussion. Using thematic analysis, we highlight barriers and facilitators to coaches appropriately removing a player from participation and parents taking their child to a physician for assessment. Contextual factors including competing priorities, emotional responses, severity of injury, parent and coach beliefs, appropriate communication, and concussion awareness can influence coach and parent concussion management strategies. Coaches, parents, and players play a vital role in facilitating concussion identification and appropriate management. While further education of coaches and parents is indicated, it is important to consider contextual factors that interfere with concussion management behaviors.